2016
DOI: 10.1016/j.celrep.2016.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Independent Histone Variant H3.3 Controls Animal Lifespan through the Regulation of Pro-longevity Transcriptional Programs

Abstract: SummaryChromatin structure orchestrates the accessibility to the genetic material. Replication-independent histone variants control transcriptional plasticity in postmitotic cells. The life-long accumulation of these histones has been described, yet the implications on organismal aging remain elusive. Here, we study the importance of the histone variant H3.3 in Caenorhabditis elegans longevity pathways. We show that H3.3-deficient nematodes have negligible lifespan differences compared to wild-type animals. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 39 publications
4
51
0
1
Order By: Relevance
“…Together with previous studies ( 31 , 32 , 49 ), our results indicate that progressive age-dependent accumulation of H3.3 variant and consequential loss of canonical H3.1/2 isoforms constitute a conserved feature of chromatin organization in slow and non-dividing cells. Although the physiological relevance of H3 variant replacement with age remains largely undefined, a recent study revealed the essential role of H3.3 in regulating pro-longevity transcriptional programs in C. elegans ( 66 ). Furthermore, lifelong H3.3 turnover was found to be involved in the regulation of neuronal activity-dependent gene expression in mouse brain ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together with previous studies ( 31 , 32 , 49 ), our results indicate that progressive age-dependent accumulation of H3.3 variant and consequential loss of canonical H3.1/2 isoforms constitute a conserved feature of chromatin organization in slow and non-dividing cells. Although the physiological relevance of H3 variant replacement with age remains largely undefined, a recent study revealed the essential role of H3.3 in regulating pro-longevity transcriptional programs in C. elegans ( 66 ). Furthermore, lifelong H3.3 turnover was found to be involved in the regulation of neuronal activity-dependent gene expression in mouse brain ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence suggest that the respiration rate induces metabolic changes, favoring alternative survival pathways as well as protective homeostatic mechanisms 43 , 53 55 . Moreover, mild mitochondrial stress induces the expression of nuclear-encoded genes through epigenetic modifications of chromatin, including posttranslational modification of histones and nucleosome turnover 56 59 . Thus, inhibition of mitochondrial respiration can mediate stress response and adaptive processes with a wide array of homeostatic functions 43 , 60 , although the engagement of this complex surveillance pathway is not a predictor of C .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that these alterations are highly related to lamin and chromatin. Therefore, biologists usually label them with fluorescence proteins and use the fluorescence images to study aging [58]. …”
Section: Introductionmentioning
confidence: 99%